Enzyme-Catalyzed Synthesis and Characterization of Dihydroxystearic Acid Ester from Palm-Based Dihydroxystearic Acid and Monohydric Alcohol - Awang, Roila (2002)
Enzymatic synthesis of dihydroxystearic acid ester (DHSA ester) from dihydroxystearic acid (DHSA) and monohydric alcohol in organic solvent were investigated. Five commercial immobilized enzyme (Lipozyme 1M, Novozym 435, Termamyl, Savinase and Lipolase) were tested for their suitability for the reaction. Among the enzymes tested, Lipozyme 1M and Novozym 435 were chosen for optimization studies because of their higher specific activity. The effect of various reaction parameters such as time, temperature, organic solvent, amount of enzyme, mole ratio of substrates, thermodynamic water activity (aw) and structure of substrates were studied to determi ne optimal condition for the produ ction of DHSA ester. The optimal conditions for DHSA ester synthesis using Lipozyme 1M and Novozym 435 were obtained at reaction time of 3h, temperature of 50°C, mole ratio of substrates, 2.0 and amount of enzyme, 10-20% (w/w). The maxi m u m conversion for Lipozyme 1M and Novozym 435 at optimal condition was 92.4% and 94.9% respectively without removal of water in the reaction mixture. The results clearly demonstrated that both enzymes are well suited for the preparation of DHSA ester in organic media. This esterification reaction follows Michaelis-Menten kinetics as observed from the relationship of initial rate of the reaction, both as a function of enzyme and of substrate concentration. The kinetics of the enzymatic reaction is suggested to agree with a Ping-Pong Bi Bi mechanism. In a 5L batch reactor, up to 90% conversion was obtained at the optimal condition. Lipozyme 1M remained active after repeated used of 12 times. Characteristics and properties of DHSA ester were also eval uated, which include heat and colour stability, solubility, irritancy, dispersibility as well as emulsification properties. Purified DHSA ester showed higher heat stability compared to crude DHSA ester. Solubility of DHSA ester in methanol and ethanol is comparatively lower as compared to the solubility at higher chain length of alcohol. This compound is non-irritant to the skin. DHSA ester seems to have some emulsifying properties in water-in-oil system with high or low content of oil phase. The composition of the oil phase is important, as castor oil seems the most compatible oil. DHSA ester could be used as stabilizer or co-emulsifier in oil-in water emulsion system.